Life in the dark: far‐red absorbing cyanobacteria extend photic zones deep into terrestrial caves. (9th September 2019) - Behrendt, Lars; Trampe, Erik L.; Nord, Nadia B.; Nguyen, Jen; Kühl, Michael; Lonco, Danijela; Nyarko, Alex; Dhinojwala, Ali; Hershey, Olivia S.; Barton, Hazel
Summary: Chlorophyll (Chl) f and d are the most recently discovered chlorophylls, enabling cyanobacteria to harvest near‐infrared radiation (NIR) at 700–780 nm for oxygenic photosynthesis. Little is known about the occurrence of these pigments in terrestrial habitats. Here, we provide first details on spectral photon irradiance within the photic zones of four terrestrial cave systems in concert with a detailed investigation of photopigmentation, light reflectance and microbial community composition. We frequently found Chl f and d along the photic zones of caves characterized by low light enriched in NIR and inhabited by cyanobacteria producing NIR‐absorbing pigments. Surprisingly, deeper parts of caves still contained NIR, an effect likely attributable to the reflectance of specific wavelengths by the surface materials of cave walls. We argue that the stratification of microbial communities across the photic zones of cave entrances resembles the light‐driven species distributions in forests and aquatic environments.